222 Effect of genetic line and parity of dam on litter birth weight and weaning weight in swine. (30th November 2020) - Christianson, Marcie I; Stalder, Kenneth J; Ramirez, Alejandro; Beitz, Donald; Keating, Aileen F
Abstract: The objective of this study was to evaluate the effects of parity and genetic line of the dam on her offspring and their ability to thrive until weaning. Data were obtained from 17 purebred litters and 72 crossbred litters and the parity of the dam ranged from 1-13. Parities were grouped into the following categories: parity 1, parity 2, parity 3-5, and parity 6+. Entire litters were weighed at birth and weaning (~28 days of age). Litters were grouped into four weight categories based on the time of year they were born: February, April, May, and July 2019. Data were analyzed by using mixed model methods (Proc Mixed, SAS V. 9.4, SAS Inst. Inc. Cary, NC). The birthweight model included fixed effects of parity and genetic line. Birth month was included as a random variable, and number born alive was used as a covariate. Mean litter birth weight was significantly different between parity 1 and parity 3-5 (P=0.001), parity 2 and parity 6+ (P=0.031), and parity 3-5 and parity 6+ (P=< 0.0001). The difference between parity 2 and parity 3-5 approached significance. Birthweight differed between genetic line (< 0.0001): Crossbred litter birthweight was 4.15kg greater than purebred litter birthweight. The weaning weight model included genetic line, parity, and number of pigs after fostering. Birth month was included as a random variable, and age at weaning and birth weight were used as covariates. Weaning weights for parity and genetic line did not differ (P >0.05).